Antarctic Water Tracks: Microbial Community Responses to Variation in Soil Moisture, pH, and Salinity - George, Scott F.; Fierer, Noah; Levy, Joseph S.; Adams, Byron (Frontiers in Microbiology, 2021)
Ice-free soils in the McMurdo Dry Valleys select for taxa able to cope with challenging environmental conditions, including extreme chemical water activity gradients, freeze-thaw cycling, desiccation, and solar radiation regimes. The low biotic complexity of Dry Valley soils makes them well-suited to investigate environmental and spatial influences on bacterial community structure. Water tracks are annually wetted habitats in the cold-arid soils of Antarctica that form briefly each summer with moisture sourced from snow melt, ground ice thaw, and atmospheric deposition via deliquescence and vapor flow into brines. Compared to neighboring arid soils, water tracks are highly saline and relatively moist habitats. They represent a considerable area (~5–10 km2) of the Dry Valley terrestrial ecosystem, an area that is expected to increase with ongoing climate change. The goal of this study was to determine how variation in the environmental conditions of water tracks influences the composition and diversity of microbial communities. We found significant differences in microbial community composition between on- and off-water track samples, and across two distinct locations. Of the tested environmental variables, soil salinity was the best predictor of community composition, with members of the Bacteroidetes phylum being relatively more abundant at higher salinities and the Actinobacteria phylum showing the opposite pattern. There was also a significant, inverse relationship between salinity and bacterial diversity. Our results suggest water track formation significantly alters dry soil microbial communities, likely influencing subsequent ecosystem functioning. We highlight how Dry Valley water tracks could be a useful model system for understanding the potential habitability of transiently wetted environments found on the surface of Mars.